CONTRIBUTIONS REGARDING THE DEFINITION OF THE TERM NEURAL NETWORK VS. NEURONAL NETWORK APPLICABLE IN THE ORGANIZATIONAL MANAGEMENT (Nonconventional Technologies Review, 2016)
Since there is no clear definition of the terms "neural network" and "neuronal network", this paper is aimed primarily to establish the difference between them by a rangeof comparative research.As a result, the paper  presents some argumentation regarding the differentiation and the point of views of its author, on the use of neural networks in studies and research regarding organizational management.
Keywords: neural network; artificial network; organization; neuron; artificial neuron; artificial inteligence